Development of the Hostility n Pandemic Scale (HPS): A Validity and Reliability Study - ERYİĞİT, DERYA; TUNÇ, EMİNE BURCU; ULUMAN MERT, MÜGE (IJATE-INT JOURNAL ASSESSMENT TOOLS EDUCATION, 2021)
The aim of this research is to develop Hostility in Pandemic Scale (HPS) for Turkey Population to determine the hostility levels of individuals, which is a factor affecting the mental well-being of the society during the pandemic. The study group consists of 855 individuals between the ages of 18-65 from different genders, and have experienced the pandemic process. For the construct validity of the scale results, exploratory factor analysis was conducted and a one-dimensional structure consisting of 22 items was revealed. It was determined that the variance explained by the scale showing a one-dimensional structure was 41.5%. As a result of the confirmatory factor analysis performed through a separate study group, it was revealed that all items have significant t values, and the model established according to model fit indexes has meaningful and acceptable fit values. Buss-Perry Aggression Scale was applied with HPS for the criterion validity. As a result of the criterion validity analysis, a significant relationship was found between the scale scores. The Cronbach Alpha was calculated to analyses internal consistency of the scale and a reliability level of 0.93 was obtained. The test-retest reliability results were found as 0.89. In addition, item statistics revealed that all of the scale items can discriminate well among the respondents. Results of the analysis revealed that, the Hostility Scale in Pandemic Process provides valid and reliable results.
Keywords: Hostility in pandemic; Pandemic; Hostility; Scale development; Validity; ANGER; BEHAVIOR; DISEASE; HEALTH